ANALISIS KONSEP DIRI SISWA SMA 8 PADANG DAN IMPLIKASINYA DALAM PELAYANAN BIMBINGAN DAN KONSELING - M. Putra Dinata Saragi (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
This research is motivated by the many problems students have in terms of self-concept. This study aims to describe students' self-concepts. This research uses descriptive quantitative method. population The study population was 464th grade students of XI and XII Senior High Schools in Padang. A sample of 215 people, selected by proportional stratified random sampling technique. The instrument used is a scale. The results of the validity and reliability test of the self-concept instrument stated that the research instrument was valid and reliable. Data were analyzed with descriptive statistics. The findings of this study indicate that on average the students' self-concept is in the positive category. The implications of the results of the study can be used as input to create a guidance and counseling service program.Keywords: Self-Concept, Guidance and Counseling Implications